Observing the coach-created motivational environment across training and competition in youth sport. Issue 2 (17th January 2017) - Smith, Nathan; Quested, Eleanor; Appleton, Paul R.; Duda, Joan L.
ABSTRACT: Adopting an integrated achievement goal (Nicholls, J. G. (1989). The competitive ethos and democratic education . Cambridge, MA: Harvard University Press.) and self-determination theory (Deci, E. L., & Ryan, R. M. (2000). The "what" and "why" of goal pursuits: Human needs and the self-determination of behavior. Psychological Inquiry, 11, 227–268. doi:10.1207/S15327965PLI1104_01) perspective as proffered by Duda, J. L. (2013). (The conceptual and empirical foundations of empowering coaching TM : Setting the stage for the PAPA project. International Journal of Sport and Exercise Psychology, 11, 311–318. doi:10.1080/1612197X.2013.839414), the aim of the current study was to observe empowering and disempowering features of the multidimensional motivational coaching environment in training and competition in youth sport. Seventeen grass-roots soccer coaches were observed and rated in training and competitive settings using the multidimensional motivational climate observation system (MMCOS; Smith, N., Tessier, D., Tzioumakis, Y., Quested, E., Appleton, P., Sarrazin, P., … Duda, J. L. (2015). Development and validation of the multidimensional motivational climate observation system (MMCOS). Journal of Sport and Exercise Psychology, 37, 4–22. doi:10.1123/jsep.2014-0059). In line with our hypotheses, coaches created different motivational environments in the two contexts. More specifically, coaches were observed to create a less empowering and more disempowering environment in competition compared to in training. The observed differences were underpinned by distinctive motivational strategies used by coaches in the two contexts. Findings have implications for the assessment of the coach-created motivational environment and the promotion of quality motivation for young athletes taking part in grass-roots-level sport.